Distributions of the particle/gas and dust/gas partition coefficients for seventy-two semi-volatile organic compounds in indoor environment. (June 2016) - Wei, Wenjuan; Mandin, Corinne; Blanchard, Olivier; Mercier, Fabien; Pelletier, Maud; Le Bot, Barbara; Glorennec, Philippe; Ramalho, Olivier
Abstract: Particle/gas and dust/gas partition coefficients ( K p and K d ) are two key parameters that address the partitioning of semi-volatile organic compounds (SVOCs) between gas-phase, airborne particles, and settled dust in indoor environment. A number of empirical equations to calculate the values of K p and K d have been reported in the literature. Therefore, the difficulty lies in the selection of a specific empirical equation in a given situation. In this study, we retrieved from the literature 38 empirical equations for calculating K p and K d values from the SVOC saturation vapor pressure and octanol/air partition coefficient. These values were calculated for 72 SVOCs: 9 phthalates, 9 polybrominated diphenyl ethers (PBDEs), 11 polychlorinated biphenyls (PCBs), 22 biocides, 14 polycyclic aromatic hydrocarbons (PAHs), 3 alkylphenols, 2 synthetic musks, tributylphosphate, and bisphenol A. The mean and median values of log10 K p or log10 K d for most SVOCs were of the same order of magnitude. The distribution of log10 K p values was fitted to either a normal distribution (for 27 SVOCs) or a log-normal distribution (for 45 SVOCs). This work provides a reference distribution of the log10 K p for 72 SVOCs, and its use may reduce the bias associated with the selection of a specific value or equation. Highlights: 38 empirical equations to calculate K p and K d from p L 0 and K oa were summarized. A reference distribution of log10 K p for 72 SVOCs was determined. The log10 K p values were normally distributed for 27 SVOCs. The distribution reduces the bias in choosing a specific equation to calculate K p . The ratio between K p and K d was determined using linear regression.